Kompilasi undang-undang Republik Indonesia di bidang hak kekayaan intelektual - [Tidak Terdaftar] ([Tidak Terdaftar], 2004)
Kompilasi undang-undang Republik Indonesia di bidang hak kekayaan intelektual